Antimicrobial susceptibility differences among mucoid and non-mucoid Pseudomonas aeruginosa isolates - Owlia, Parviz; Nosrati, Rahim; Alaghehbandan, Reza; Lari, Abdolaziz Rastegar (GMS Hygiene and Infection Control, 2014)
[english] is one of the most important opportunistic bacteria, causing a wide variety of infections particularly in immunocompromised patients. The extracellular glycocalyx is produced in copious amounts by mucoid strains of . Mucoid and non-mucoid strains show some differences in their antimicrobial susceptibility pattern. The aim of this study was to investigate the frequency of mucoid and non-mucoid types and their antimicrobial susceptibility patterns isolated from Milad and Mostafa Khomeini Hospital in Tehran, Iran. One hundred isolates were collected which all were confirmed by conventional biochemical tests and PCR assay using specific primers for and lipoproteins. Mucoid and non-mucoid types of isolates were determined by culturing isolates on BHI agar containing Congo red and Muir mordant staining method. The susceptibility pattern of isolates against 23 different antibiotics was assessed using MIC sensititre susceptibility plates.Fifty of 100 of isolates were mucoid type, of which 14 isolates were from Mostafa Khomeini Hospital. Frequency of mucoid type of in Mostafa Khomeini hospital (70%) was higher than that seen in Milad hospital (45%). The statistical analysis of MICs results showed significant differences in antimicrobial resistance among mucoid and non-mucoid types (non mucoid strains showed more resistance against tested antibiotics). This may be due to the tendency of some antibiotics to attach to extracellular glycocalyx of mucoid strains.